Increased Survival with Enzalutamide in Prostate Cancer after Chemotherapy - Scher, Howard I; Fizazi, Karim; Saad, Fred; Taplin, Mary-Ellen; Sternberg, Cora N; Miller, Kurt; de Wit, Ronald; Mulders, Peter; Chi, Kim N; Shore, Neal D; Armstrong, Andrew J; Flaig, Thomas W; et al. (The New England journal of medicine, 2012)
In a study involving nearly 1200 men with metastatic prostate cancer who had progressive disease after chemotherapy, enzalutamide, a novel androgen-receptor blocker, extended the median survival by nearly 5 months, as compared with placebo (18 months vs. 13 months). Prostate cancer is an androgen-dependent disease that initially responds but later becomes resistant to established therapies that reduce circulating testosterone levels or inhibit androgen binding to the androgen receptor. 1 – 4 Reactivation of the disease despite castrate levels of testosterone represents a transition to the lethal phenotype of castration-resistant prostate cancer. 5 , 6 This state was previously called androgen-independent or hormone-refractory prostate cancer but is now recognized to be driven by androgen-receptor signaling, in part due to overexpression of the androgen receptor itself. 7 , 8 In preclinical models of prostate cancer, androgen-receptor overexpression shortens the period of tumor latency and confers resistance to . . .